Pengaruh kualitas produk, harga, dan promosi terhadap keputusan pembelian mie instan merek Indomie - Nikmah Baqiyyatus Shalihah; Oktami Imtihani MK; Tri Wulandari; Rizki Hidayat; Andi Prayoga (Universitas Widya Mataram, 2022)
This research was conducted to determine the effect of product quality, price, and promotion on purchasing decision at instan noodle Indomie brand. This research is the result of a survey to students in Lampung. The sample use is 70 respondents. The process of distributing questionnaires to respondents was carried out online. This research method is quantitative and the technique used is a purposive sampling. This research uses test data validity and reliability tests. This research was analyzed with Smart PLS program. This results of the analysis obtained show that the product quality, price, and promotion variable has a positive and significant effect on purchasing decision instan noodle Indomie brand. And the price variable is the most dominant on purchasing decisions compared to other variable.